Experimental study on global visualization of loop heat pipe with a flat disk-shaped evaporator. (November 2022) - Zhao, S.C.; Zhang, Z.K.; Zhao, R.Z.; Liu, Z.C.; Liu, Wei
Abstract: In this study, a prototype of a flat-disk global visualisation loop heat pipe was constructed, and the two-phase working phenomenon in the system operation was elaborated. This study focuses on a new method for global visualisation of loop heat pipes. The evaporator, condenser, and pipeline are integrated into a single piece of glass. Deionised water was used as the working fluid. Simultaneously, the airtightness of the system was guaranteed. During the experiment, an infrared thermal imager and a high-definition camera were used to collect optical information. The heat and mass transfer phenomena in the system under different working conditions were experimentally studied. The three stages of the loop heat pipe start-up were analysed according to the change in the vapour–liquid state. Through global observation of the heat and mass transfer process, the effects of condenser working efficiency, heat leakage, and non-condensable gas on the thermal performance of the loop heat pipe were studied. During the test, the temperature of the heating surface was lower than 92 °C, and the heat load range of the system was 25–45 W. The condenser was designed as a fan-tube condenser with forced convection heat dissipation. The system achieved self-regulation and stability through the cooperation of various components. The significance of this study is that the global visualisation of the loop heat pipe comprehensively describes the heat and mass transfer process of the system, and the operating characteristics of the loop heat pipe were studied intuitively. Highlights: A flat-disk global visualisation loop heat pipe is designed by using quartz glass. Silicone rubber seals are used to ensure the air tightness of the system. Studying the system operation mechanism, dividing the start-up into three stages. Various working conditions and coordinated changes are observed by the experiment. The heat load is between 25 W and 45 W with the system temperature below 92 ℃.